Simulation of Fe2O3/Al combustion: sensitivity analysis - Brito, Paulo (2010)
The self-propagating high temperature reactions, as the Fez03/AI thermite combustion, are hard to follow by experimentation due to the extreme conditions that characterize them. Hence, theoretical prediction of these processes represents a valuable guideline for experimental work. The availability of experimental results of radial combustion on disk shaped samples (Durães et aI., 2006a) has stimulated the derivation of a onedimensional model to describe the FeZ03/AI combustion radial propagation (Durães et aI., 2006b). This model considers non-steady combustion propagation on thin circular samples of FeZ03/AI mixtures, zero order kinetics and conductive/radiative heat transfer. Ali the properties of the system vary with the temperature and composition during the propagation. Phase transitions are also contemplated. These last features allowed the obtainment of realistic solutions, readily comparable with the experimental values presented in Durães et aI. (2006a). Adaptive numerical methods were applied in the resolution. The solution profiles are fast moving steep fronts, which were validated by experimental results in Durães et aI. (2006b). The experimental combustion velocities were used to adjust the kinetic constant of the model, in order to give ita good predictive capability.